REGRESI NONPARAMETRIK MENGGUNAKAN METODE ROBUST DAN CROSS-VALIDATION (STUDI KASUS MAHASISWA STIA MUHAMMADIYAH SELONG) - Ratna Yuniarti; Widya Hartati (Unisda Journal of Mathematics and Computer Science (UJMC), 2017)
This paper is about comparison of estimation regression function between nonparametric regression kernel using Nadaraya Watson estimator with simple linearregression. In addition, a long-time case study was given in obtaining the first job. The data used are fresh graduate student, of Public Administration departement in STIA Muhammadiyah Selong graduate 2016. In this case we will see the relation between Cumulative Achievement Index (X) with long waiting time to get the job (Y). The software statistics with the help of software applications R. For the selection of the best model is by Cross-Validation. In this paper, given the theory and prove about crossvalidation method are described. And then, this paper describes the Robust method if there is outlier.